1982
DOI: 10.1002/1097-0142(19821201)50:11<2433::aid-cncr2820501131>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial metastases in small cell carcinoma of the lung. Correlation of clinical and autopsy findings

Abstract: Two hundred‐twelve consecutive patients with small cell carcinoma of the lung were included in an evaluation of clinical and diagnostic neurologic findings of intracranial metastases. A correlation of premortem findings to postmortem examination of the brain was obtained in 87 of the patients. Clinical intracranial metastases were diagnosed in 21.2% on the basis of symptoms and signs. At autopsy 44 of the 87 patients (50%) had metastases. Lesions located to the posterior cranial fossa were demonstrated in 53% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
1

Year Published

1983
1983
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(27 citation statements)
references
References 6 publications
0
26
1
Order By: Relevance
“…Multiple brain metastases are frequently observed with small-cell lung carcinoma (Hirsch et al, 1982), distributed more often in the frontal, parietal, and occipitotemporal regions than in the temporal or occipital lobes, and occasionally in the basal ganglia (Delattre et al, 1988). The metastases noted in LM's brain had a similar distribution (8 in frontal cortex, 11 in parietal cortex, 5 in temporal cortex, and 5 in occipitotemporal cortex).…”
Section: Patient Lmmentioning
confidence: 99%
“…Multiple brain metastases are frequently observed with small-cell lung carcinoma (Hirsch et al, 1982), distributed more often in the frontal, parietal, and occipitotemporal regions than in the temporal or occipital lobes, and occasionally in the basal ganglia (Delattre et al, 1988). The metastases noted in LM's brain had a similar distribution (8 in frontal cortex, 11 in parietal cortex, 5 in temporal cortex, and 5 in occipitotemporal cortex).…”
Section: Patient Lmmentioning
confidence: 99%
“…With prolonged survival the probability of CNS disease has increased from 15% at the time of diagnosis to 50% after one year, as reported by Nugent et al and Hirsch et al (3,4). At autopsy the frequency of CNS metastases is far greater than that diagnosed in vivo (5).…”
Section: Introductionmentioning
confidence: 69%
“…A meta-analysis of PCI in patients with complete remission after systemic treatment demonstrated a slight survival benefit of above 5% with PCI [42]. In addition, a more recent phase III trial performed by SLOTMAN et al [50] in patients with extensive disease and performance status 0-2 showed that, in patients who responded to chemotherapy (not only patients with complete response), PCI decreased the incidence of brain metastases from 40.4% at 1 year to 14.6% (hazard ratio (HR) 0.27, 95% CI 0.16-0.44; p,0.0001) and gave a survival and symptomatic benefit with a 1-year survival rate of 13.3% in the control group and 27.1% in the treated group (HR 0.68, 95% CI 0.52-0.88; p50.003).…”
Section: Prophylactic Cranial Irradiationmentioning
confidence: 99%